Rút gọn các biểu thức sau a) 3x(3x-5)+4x-9x^2 b)(2x+3)^2+(2x-5)(2x+5)

Rút gọn các biểu thức sau
a) 3x(3x-5)+4x-9x^2
b)(2x+3)^2+(2x-5)(2x+5)

2 bình luận về “Rút gọn các biểu thức sau a) 3x(3x-5)+4x-9x^2 b)(2x+3)^2+(2x-5)(2x+5)”

  1. $a)3x(3x-5)+4x-9x^2$
    $=9x^2-15x+4x-9x^2$
    $=-11x$
    $b)(2x+3)^2+(2x-5)(2x+5)$
    $=4x^2+12x+9+4x^2-25$
    $=8x^2+12x-16$
    Chúc bạn học tốt !!!
     

    Trả lời
  2. Giải đáp:
     
    Lời giải và giải thích chi tiết:
      a) 3x(3x-5)+4x-9x² 
    = 9x²-15x+4x-9x²
    = (9x²-9x²)-(15x-4x)
    = -11x
      b) (2x+3)^2+(2x-5)(2x+5)
    = 4x²+12x+9+4x²-25
    = (4x²+4x²)+12x+(9-25)
    = 8x²+12x-16

    Trả lời

Viết một bình luận

Câu hỏi mới